What can we learn from the online learning experiences of medical students in Poland during the SARS-CoV-2 pandemic? - Anna Pokryszko-Dragan; Karol Marschollek; Marta Nowakowska-Kotas; Gillian Aitken (BMC Medical Education, 2021)
Abstract Background In March 2020, due to the SARS-CoV-2 pandemic, the Polish government ordered the closing of all medical faculties, with an obligatory shift to online learning. This lockdown continued, with a short period of blended learning, over the time of summer 2020. Distance learning had previously been rarely used within Polish medical schools, so such a sudden transfer was a major challenge. The aim of the study was to explore undergraduates’ perception of online teaching provided at Polish medical faculties during the pandemic and to analyze how these experiences may inform future curriculum development. Methods The online survey was addressed to undergraduates at Polish medical faculties in November 2020. The questions captured demographics, epidemiological data and students’ perception of various aspects of online teaching. Responses were subjected to thematic analysis and their distribution compared considering demographic parameters . Results Six hundred twenty students from thirteen medical faculties responded to the survey. Major benefits from online teaching perceived by respondents included increased convenience, enhanced quality, a sense of comfort and safety. Major complaints were associated with unsatisfactory content, technical issues, difficulties engaging, poor organization and lack of social life. Students claimed that online teaching required more self-directed learning and discipline and 57.9% considered this impact as negative. 44.5% of respondents took part in educational online activities beyond their scheduled classes. For 49.2% online examinations were reported as more stressful and for 24.8% - less stressful than traditional ones. Differences in the opinions on online teaching were found between men and women, students in early and senior years, Polish and non-Polish ones. Conclusions The sudden move online inevitably was problematic for students. Their perspective afforded us the opportunity to consider shortcomings of pre-pandemic undergraduate curriculum. Online education requires a more self-directed learning, which was challenging for many students, so further enhancement of more autonomous study skills seems necessary. Distress expressed by students indicates the need for urgent support with mental health issues.